JMJD6 is a tumorigenic factor and therapeutic target in neuroblastoma - Matthew Wong (Nature Portfolio, 2019)
Although the gain in chromosome 17q21-ter is commonly associated with neuroblastoma, it is not clear which gene of this region mediates tumorigenesis. Here, the authors are showing that JMJD6, which locates in that region, is a neuroblastoma tumorigenic factor.